Estimating active drag based on full and semi-tethered swimming tests - Cortesi, M.; Gatta, G.; Carmigniani, R.; Zamparo, P. (Journal of Sports Science & Medicine, 2023)
During full tethered swimming no hydrodynamic resistance is generated (since v = 0) and all the swimmer`s propulsive force (FP) is utilized to exert force on the tether (FT = FP). During semi-tethered swimming FP can be made useful to one of two ends: exerting force on the tether (FST) or overcoming drag in the water (active drag: Da). At constant stroke rate, the mean propulsive force (FP) is constant and the quantity FP - FST (the "residual thrust") corresponds to Da. In this study we explored the possibility to estimate Da based on this method ("residual thrust method") and we compared these values with passive drag values (Dp) and with values of active drag estimated by means of the "planimetric method". Based on data obtained from resisted swimming (full and semi-tethered tests at 100% and 35, 50, 60, 75, 85% of the individual FT), active drag was calculated as: DaST = kaST .vST2 = FP - FST ("residual thrust method"). Passive drag (Dp) was calculated based on data obtained from passive towing tests and active drag ("planimetric method") was estimated as: DaPL = Dp.1.5. Speed-specific drag (k = D/v2) in passive conditions (kp) was )25 kg.m-1 and in active conditions (ka) )38 kg.m-1 (with either method); thus, DaST > Dp and DaST > DaPL. In human swimming active drag is, thus, about 1.5 times larger than passive drag. These experiments can be conducted in an ecological setting (in the swimming pool) by using basic instrumentation and a simple set of calculations.